2008
DOI: 10.1057/ijea.2008.14
|View full text |Cite
|
Sign up to set email alerts
|

White Corporate Philanthropy and Its Support of Private Black Colleges in the 1960s and 1970s

Abstract: This paper traces the rise of corporate philanthropy in terms of its support of Black colleges, explores fi nancial support overall of Black colleges during the 1960s and 1970s, and describes the relationships between corporations and private Black college leaders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…( Carnegie, 1889( Carnegie, /2008 The concept that giving was primarily the job of wealthy philanthropistsand not of corporations -was the status quo in American philanthropy before World War I; and even after the war, most corporations failed to ' take advantage of the federal government ' s deduction provision, made law in 1935 ' ( Gasman and Drezner, 2008, p. 80 ). Direct corporate giving did not become a substantial player in American philanthropy until the post-World War II era ( Gasman and Drezner, 2008 ). Yet still, critics at the neoliberal end of the philosophical spectrum continued to speak out against its practice.…”
Section: Us Corporate Engagement In Philanthropymentioning
confidence: 99%
See 1 more Smart Citation
“…( Carnegie, 1889( Carnegie, /2008 The concept that giving was primarily the job of wealthy philanthropistsand not of corporations -was the status quo in American philanthropy before World War I; and even after the war, most corporations failed to ' take advantage of the federal government ' s deduction provision, made law in 1935 ' ( Gasman and Drezner, 2008, p. 80 ). Direct corporate giving did not become a substantial player in American philanthropy until the post-World War II era ( Gasman and Drezner, 2008 ). Yet still, critics at the neoliberal end of the philosophical spectrum continued to speak out against its practice.…”
Section: Us Corporate Engagement In Philanthropymentioning
confidence: 99%
“…This notion was the premise of a New Jersey Supreme Court decision in 1953 in which several shareholders of the A.P. Smith Manufacturing Company questioned the legality of the company ' s donation to Princeton University; the court held that ' corporations were permitted to make contributions where the activity being promoted by the gift promoted the goodwill of the business of the corporation ' (Supreme Court of New Jersey, 1953;Gasman and Drezner, 2008 ).…”
Section: Us Corporate Engagement In Philanthropymentioning
confidence: 99%
“…Continuing an interest in the strategies for fundraising in the black college community and the racial dynamics of raising funds in the mid-twentieth century, Gasman and Drezner (2008 explored the work of the Oram Group, a for-profit fundraising organization with a penchant for working with HBCUs. Gasman and Drezner focused their attention on several historic campaigns at HBCUs and the role of leadership, boards of trustees, and community relations in fundraising.…”
Section: A History Of Fundraisingmentioning
confidence: 99%
“…Interestingly, this historical research reveals discrimination by corporations and foundations allocating funds to higher education, with HBCUs, save for a few examples, garnering substantially less money in their efforts to raise funds (Gasman and Drezner, 2008). Moreover, Gasman and Drezner (2008 found that HBCUs have not solicited their alumni in any systematic way, believing that this population did not have access to funds.…”
Section: A History Of Fundraisingmentioning
confidence: 99%
See 1 more Smart Citation